PENGARUH MOTIVASI KERJA, KOMUNIKASI DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Poniasih, Ni Luh Gede; Dewi, A.A. Sagung Kartika (E-Jurnal Manajemen, 2015)
Job satisfaction in the company viewed from a lack of morale in completing the work, which is influenced by variables of work motivation, communication and employee stress. Thisostudy aimedoto influence workomotivation, communication andiwork stress on employee job satisfaction simultaneouslyior partiallyiand determine which variables are dominant effect. Location research PT. Indonesia Power UBP Bali, a sample of 150 employees with a simple random sampling method. The collection of data through observation, interviews and questionnaires, the multiple linear regression analysis technique. Results showed variable work motivation, communicationiandiwork stress simultaneously and partiallyisignificant effection employee jobisatisfaction. For further research could use more accurate analysis techniques, as well as adding another variable that is contributing to the problem that occurred as the employment relationship.
Keywords: work motivation; communication; job stress; job satisfaction.